indonesia - Hidayat, Taufiq; Azahari, Raihanah; Fauzi, Fauzi (Al-Risalah, 2020)
The high price of jeulame or dowry in wedding tradition in Banda Aceh results in general assumption between societies that it contradicts the basic purpose of sharia. This article tries to investigate the agreement between traditional rules and sharia principles in terms of wedding regulations in Banda Aceh through several formulations of research problems: first, how is the determination of jeulame in Banda Aceh?; second, how is the application of jeulame in Banda Aceh?; third, what the common thread between traditional rules and sharia principles in terms of jeulame’s amount in marriage? This is field research. The interview is conducted towards some religious leaders, traditional figures, experts, and some inhabitants who are married couples. This research concludes that the amount of jeulame in Banda Aceh ranges between 6 and 20 manyam of gold. The amount of jeulame depends on the education, family, and social backgrounds of women. Although there are several disagreements, this research reveals that the agreement between traditional rules and sharia in terms of marriage regulations is centered on three choosable levels (low, medium, high) in which each family of two subjects (man and woman) can choose one of them without being burdened. Therefore, there is no contradiction between traditional rules and sharia principles.